APPLICATION OF FÜCHTBAUER–LADENBURG EQUATION AND RECIPROCITY METHOD FOR DETERMINATION OF EMISSION CROSS SECTIONS OF ND-DOPED LASER MEDIA - M. P. Demesh; N. V. Gusakova; A. S. Yasukevich; N. V. Kuleshov; S. V. Grigor`ev; Y. A. Krot; M. V. Kosmyna; A. N. Shekchotsov (Приборы и методы измерений, 2015)
Rare-earth doped crystals with broad bands of gain spectra are attractive for femtosecond laser applications. Therefore, for this purposes crystals with disordered structure are of great interest. In this article we investigate laser-related spectroscopic properties of new trigonal crystals Nd3+:Ca10K(VO4 )7 (Nd:CKV), Nd3+:Ca9 La(VO4 )7 (Nd:CLaV) и Nd3+:Ca10Li(VO4 )7 (Nd:CLiV). The Füchtbauer-Ladenburg equation and the integral reciprocity method were applied for determination of stimulated emission cross section spectra for Nd3+ ions. The maximum values of emission cross sections and bandwidth (FWHM) near λ = 1,07 μm are 9,33·10 -20cm2 (σ – polarization, Nd:CKV) and 30 nm (π – polarization, Nd:CKV), near λ = 1,35 μm – 1,55·1020cm2 and 50 nm (π – polarization, Nd:CKV). The broad and smooth bands of the gain spectra in the regions near 1,07 and 1,35 μm make it possible to generate ultra short light pulses with duration of about 60 fs (1,07 µm) and 45 fs (1,35  µm) in the mode-locking regime.